Piper aduncum leaves ethanol extracts protective effect compared with silymarin in liver cirrhosis induced in rats - Arroyo, Jorge (2012)
Objectives: To determine the protective effect of Piper aduncum (matico) leaves ethanol extract and its phytomedicine in capsules in liver cirrhosis induced in rats. Design: Experimental. Location: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Leaves of Piper aduncum, and Rattus norvegicus, Holtzman strain. Interventions: The leaves were collected in La Merced district, Pasco department. The phytomedicine capsules were prepared from the plant ethanol extract. Cirrhosis was induced with phenobarbital 0.5 mg/mL diluted in drinking water during 15 days, then carbon tetrachloride 0.2mL/kg 1:1 in olive oil orally during 7 days. Blood samples were drawn in order to determine liver profile and malondialdehyde; the animals were sacrificed, extracting the liver for pathology study. Data were evaluated by multivariate techniques with p <0.05. Main outcome measures: Degree of liver injury, biochemical marks, oxidative stress. Results: About 200 mg/kg of both extract and phytomedicine decreased ALT values (p < 0.621), total bilirrubin (p < 0.385) and direct bilirrubin (p < 0.283) and increased total protein (p <0.539) and albumin (p <0.114), similar to silymarin group. Collagen, fibrosis and liver damage degree increased with carbon tetrachloride, and reduced with the different treatments and silymarin. Oxidative stress marker was also reduced with the applied treatments (p <0.002). Conclusions: Piper aduncum (matico) leaves ethanol extract and its phytomedicine had protective effect of cirrhosis induced in rats similar to silymarin.